Comparison between the QRMA Measurement with the Anamnesis and the Capillary Blood Glucose Test - Muflih Muflih; Suwarsi Suwarsi; Fajarina Lathu Asmarani (Universitas Airlangga, 2019)
ABSTRACTIntroduction: The examination of patients with diabetes mellitus (DM) can be done by reviewing their complaints and through a capillary blood glucose level test to determine the value of their Random Blood Glucose Level. QRMA (Quantum Resonance Magnetic Analyzer) is claimed to be able to check the patient’s bodily condition (including blood glucose) with an accuracy of 85%. The purpose of this study was to verify the validity of the QRMA tool and its accuracy by comparing the results of the anamnesis and the examination conducted using the capillary blood glucose test method.Methods: The research method used was a cross-sectional design. The total sample consisted of 44 respondents in the working area of the Community Health Centers in Yogyakarta with the risk factor being blood sugar level instability. The sampling technique used was purposive sampling. The main variable in this study was the value of the blood sugar level measured based on the coefficient value of the QRMA tool and the value of Random Blood Glucose obtained through the capillary blood glucose test.Results: The blood glucose value was not correlated significantly with the coefficient value of QRMA. The value of blood glucose when examined alongside the result of the respondent's anamnesis showed there to be a significant difference. The value of the QRMA coefficient when examined against the results from the history of the respondents showed no significant difference. Linear regression showed that the variables of height, body weight, and IMT had a correlation with the QRMA coefficient value.Conclusion: The QRMA tool was not able to provide a picture of the actual condition of the blood glucose level of the respondents when compared with the results of the anamnesis and the blood glucose value from the capillary blood glucose test. Non-invasive health measurement devices such as QRMA are not used by nurses as a standard for determining the health status of DM patients.